THE FOUR YEARS AGO OF WORLD CRISIS, THE DARK CLOUDS ARE STILL THERE - Herrera García, Beatriz (2012)
At the end of the third quarter of 2012, the global economic situation remains a challenge, with increased risk of a severe recession. Four major weaknesses of the global economy continue to plot against a robust economic recovery in developed economies, creating a vicious circle: i) The deleveraging of banks, companies and households continue to constrain normal credit flows and consumption as well as investment demand; ii) Unemployment remains high, a condition that is both cause and effect in the prevention of economic recovery; iii) fiscal austerity responses to growing sovereign debt discourage economic growth and a return to debt sustainability of all, making everything more difficult, and iv) The banks exposures and sovereign debt perpetuate the fragility of the financial sector, and reinforce the continued deleveraging.